KETERAMPILAN MENGKOMUNIKASIKAN HASIL PRAKTIKUM MAHASISWA CALON GURU BIOLOGI - Ita, Ita; Saputri, Andini Mega (Universitas Islam Balitar, 2021)
This study aims to describe the skills of communicating the results of practicum by prospective biology teacher students and identify the obstacles faced by prospective biology teacher students in communicating the results of practicum. Descriptive research with data obtained from the value of the practicum report and analyzed descriptively categorically. Data mining was also carried out through interviews with students whose practicum report scores were low. The results showed that the skills of prospective biology teacher students in compiling practicum reports were in a fairly good category (44.12%). The low skill of students based on these findings is because there are several obstacles faced by students when compiling a practicum report as a form of written communication. Understanding of how to write a practicum report and students' mastery of the material that is the topic of practicum are factors that affect the communication skills found in this study.